Pelikula a documentary on Philippine film : 1897-1960 - Cultural Center of the Philippines; Sotto, Agustin (Manila The Center, 1992)
Explores the origins of local Philippine film and cinema from the late 19th century until the mid-20th century. Discusses key contributors and films, as well as their social and political influences on society.
VHS.
Narration, Joonee Gamboa ; producers, Rowena E. Concepcion, Mary Ann Ines-Loveria.
In Tagalog with English narration.
Keywords: Motion pictures -- History. -- Philippines; Documentary